Slc25a17 Gene Trapped Mice: PMP34 Plays a Role in the Peroxisomal Degradation of Phytanic and Pristanic Acid - Van Veldhoven, Paul P.; de Schryver, Evelyn; Young, Stephen G.; Zwijsen, An; Fransen, Marc; Espeel, Marc; Baes, Myriam; Van Ael, Elke (Frontiers in Cell and Developmental Biology, 2020)
Mice lacking PMP34, a peroxisomal membrane transporter encoded by Slc25a17, did not manifest any obvious phenotype on a Swiss Webster genetic background, even with various treatments designed to unmask impaired peroxisomal functioning. Peroxisomal alpha- and beta-oxidation rates in PMP34 deficient fibroblasts or liver slices were not or only modestly affected and in bile, no abnormal bile acid intermediates were detected. Peroxisomal content of cofactors like CoA, ATP, NAD+, thiamine-pyrophosphate and pyridoxal-phosphate, based on direct or indirect data, appeared normal as were tissue plasmalogen and very long chain fatty acid levels. However, upon dietary phytol administration, the knockout mice displayed hepatomegaly, liver inflammation, and an induction of peroxisomal enzymes. This phenotype was partially mediated by PPARα. Hepatic triglycerides and cholesterylesters were elevated and both phytanic acid and pristanic acid accumulated in the liver lipids, in females to higher extent than in males. In addition, pristanic acid degradation products were detected, as wells as the CoA-esters of all these branched fatty acids. Hence, PMP34 is important for the degradation of phytanic/pristanic acid and/or export of their metabolites. Whether this is caused by a shortage of peroxisomal CoA affecting the intraperoxisomal formation of pristanoyl-CoA (and perhaps of phytanoyl-CoA), or the SCPx-catalyzed thiolytic cleavage during pristanic acid beta-oxidation, could not be proven in this model, but the phytol-derived acyl-CoA profile is compatible with the latter possibility. On the other hand, the normal functioning of other peroxisomal pathways, and especially bile acid formation, seems to exclude severe transport problems or a shortage of CoA, and other cofactors like FAD, NAD(P)+, TPP. Based on our findings, PMP34 deficiency in humans is unlikely to be a life threatening condition but could cause elevated phytanic/pristanic acid levels in older adults.